Inflammatory microenvironment and human papillomavirus-induced carcinogenesis. (August 2016) - Mangino, Giorgio; Chiantore, Maria Vincenza; Iuliano, Marco; Fiorucci, Gianna; Romeo, Giovanna
Highlights: Inflammatory cancer microenvironment. Inflammation and HPV-induced tumorigenesis. Immune molecules, microRNAs and their delivery by microvesicles. Abstract: More than 15% of the global cancer burden is attributable to infectious agents. Pathogens that cause persistent infections are strongly associated with cancer, inflammation being a major component of the chronic infections as revealed by basic, clinical and epidemiological studies. Persistent infection and viral oncoproteins induce specific cellular pathways modifications that promote tumorigenesis. Deregulated and continuous immune response leads to severe tissue and systemic damage, impaired tumor surveillance and consequent carcinogenesis promotion by selecting for metastatic and therapeutically resistant tumor phenotypes. In this review, the role of inflammatory microenvironment in the HPV-induced carcinogenesis is addressed, with a specific focus on the involvement of the immune molecules and microRNAs as well as their delivery through the microvesicle cargo.